2010
DOI: 10.1002/etc.299
|View full text |Cite
|
Sign up to set email alerts
|

The effect of natural dissolved organic carbon on the acute toxicity of copper to larval freshwater mussels (glochidia)

Abstract: The present study examined the effect of dissolved organic carbon (DOC), both added and inherent, on Cu toxicity in glochidia, the larvae of freshwater mussels. Using incremental additions of natural DOC concentrate and reconstituted water, a series of acute copper toxicity tests were conducted. An increase in DOC from 0.7 to 4.4 mg C/L resulted in a fourfold increase (36 150 mg Cu/L) in the 24 h median effective concentration (EC50) and a significant linear relationship (r 2 0.98, p 0.0008) between the DOC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Cherry et al (1991) summarized these events, highlighting that Cu was detrimental to mussel growth and physiological activity at water concentrations in the 15-20 lg/l range, with acutely toxic effects noted at 19.4 lg/l. Additional research reported Cu-acute toxicity levels (median effective concentrations, EC50s) as low as 17-36 lg/l for native freshwater mussels (Jacobson et al, 1993;Gillis et al, 2010).…”
Section: Metalsmentioning
confidence: 99%
“…Cherry et al (1991) summarized these events, highlighting that Cu was detrimental to mussel growth and physiological activity at water concentrations in the 15-20 lg/l range, with acutely toxic effects noted at 19.4 lg/l. Additional research reported Cu-acute toxicity levels (median effective concentrations, EC50s) as low as 17-36 lg/l for native freshwater mussels (Jacobson et al, 1993;Gillis et al, 2010).…”
Section: Metalsmentioning
confidence: 99%
“…Shrimp survival in AMD water substantially increased in the presence of both 10 and 20 mg/L AHA. Decreases in toxicity of heavy metals to invertebrates and fish have been shown to occur in the presence of HS (Dobranskyte et al 2006;Gillis et al 2010;Schwartz et al 2004). The decrease in toxicity of heavy metals in the presence of dissolved organic carbon (DOC), such as HS, has been (2005) Dashes not tested a Dissolved metals b Total metals recorded (Chapman and Simpson [2005]) suggested to be due to the complexation of metals by DOC.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that the presence of high amounts of HS in naturally acidic waterways buffers the organisms present against the detrimental effects of low pH (Collier et al 1990; Dangles et al 2004). HS have also been shown to decrease the toxicity of heavy metals to aquatic organisms across a number of different trophic levels (Gillis et al 2010;Kim et al 1999;Schwartz et al 2004). Despite this, the ability of HS to increase survival to anthropogenically acidified waters, such as those affected by AMD, is unknown.…”
mentioning
confidence: 95%
“…Dissolved organic carbon (DOC) and other sources of organic material can bind to aqueous Cu, reduce its bioavailability, and ameliorate toxicity (Allen et al 1980;Erickson et al 1996;Schwartz et al 2004). Increasing levels of DOC in laboratory exposures have been shown to reduce Cu toxicity to molluscs (Gillis et al 2008(Gillis et al , 2010Wang et al 2009). In the Parental Exposure, all replicates were fed identical quantities of spinach and contained the same number of snails, in an effort to limit variation in organic matter and thus variation in bioavailable Cu.…”
Section: Adult Survival and Qualitative Behaviormentioning
confidence: 99%
“…As this is not an exhaustive evaluation of Cu in the environment, it is important to note other modifying factors that can affect bioavailability and thus the toxicity of Cu in natural aquatic systems. For example, Gillis et al (2010) reported that Cu EC50s were up to three-fold higher when freshwater mussel glochidia were exposed in Cuaugmented natural water compared to Cu-augmented reconstituted laboratory water. While we cannot comment on how frequently Cu concentrations in the environment may exceed the multigenerational effect concentrations reported here without accounting for possible modifying factors, our study demonstrates that even one pulse event at potentially environmentally relevant concentrations can cause significant detriment to the next generation.…”
Section: Juvenile Survival and Copper Sensitivitymentioning
confidence: 99%